Sialic acid-binding lectins: submolecular specificity and interaction with sialoglycoproteins and tumour cells - Fischer, Edgar; Brossmer, Reinhard (Glycoconjugate journal, 1995)
We examined the specificity of limulin,Limax flavus agglutinin (LFA) andSambucus nigra agglutinin I (SNA I) at the submolecular level of sialic acid, and characterized their interactions with a panel of structurally distinct sialoglycoproteins. In haemagglutination inhibition assays NeuAc-α-glycosides were stronger inhibitors for limulin and LFA than nativeN-acetylneuraminic acid (NeuAc). TheN-acetyl of NeuAc was crucial for binding to both lectins. N-thioacetylated NeuAc lost affinity for LFA, but still bound to limulin. Thus, distinct intermolecular interactions are involved in binding of sialic acid to the lectins. The glyceryl side chain was required for interaction with LFA, but not with limulin. SNA I specifically bound NeuAcα2 → 6Galα1 → 4Glc, but not monomeric sialic acids. Limulin and LFA strongly interacted with O-chain glycoproteins, whereas SNA I preferred N-chain proteins that carry NeuAcα2 → 6 residues. The lectins were compared with those fromCepaea hortensis andTachypleus tridentatus (TTA) and to wheat-germ agglutinin, and were then used to probe tumour cell lines for cell surface sialylation. With the exception of TTA, all lectins interacted with the tumour cells. Limulin distinguished between the low (Eb) and highly (ESb) metastatic mouse lymphoma lines by selectively agglutinating sialidase-treated ESb cells.
Gesehen am 27.06.2024